2011
DOI: 10.1111/j.1532-950x.2010.00789.x
|View full text |Cite
|
Sign up to set email alerts
|

Canine Spinal Nephroblastoma: Long‐Term Outcomes Associated with Treatment of 10 Cases (1996–2009)

Abstract: Results of this observational study suggest that surgical cytoreduction and radiotherapy are effective at improving survival in dogs with CSN, and that ID-EM tumors may be associated with a more favorable prognosis than IM neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 35 publications
(141 reference statements)
1
55
0
8
Order By: Relevance
“…105,106 In one large retrospective study of 399 histopathologically confirmed spinal cord tumors in dogs, 48% were extradural, 13% were intradural/extramedullary, 6% were intramedullary, and 33% were mixed compartment. 105,106,111,112 Spinal lymphoma often affects young cats, is often associated with the feline leukemia virus (FeLV), tends to occur in the thoracic and lumbar spine, and is usually present in multiple extraneural locations. 105,106 Meningiomas and malignant nerve sheath tumors (MNSTs) arise most frequently in the cervical spinal cord, and MNSTs are especially prominent in the cervical intumescence area.…”
Section: Incidence and Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…105,106 In one large retrospective study of 399 histopathologically confirmed spinal cord tumors in dogs, 48% were extradural, 13% were intradural/extramedullary, 6% were intramedullary, and 33% were mixed compartment. 105,106,111,112 Spinal lymphoma often affects young cats, is often associated with the feline leukemia virus (FeLV), tends to occur in the thoracic and lumbar spine, and is usually present in multiple extraneural locations. 105,106 Meningiomas and malignant nerve sheath tumors (MNSTs) arise most frequently in the cervical spinal cord, and MNSTs are especially prominent in the cervical intumescence area.…”
Section: Incidence and Risk Factorsmentioning
confidence: 99%
“…117 As with RT for intracranial tumors, the trend has been to reduce the dose per fraction and increase the total dose. 111,112,121 The results reported for surgery alone are widely variable with MSTs of 70.5 days and 380.5 days. Also, there is a dose-volume relationship, and the length of the spinal cord irradiated has to be considered when prescribing the dose.…”
Section: Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in cases of intramedullary tumors, the ideal is to make a preoperative planning based on some method of advanced neuroimaging, such as CT and MRI, to know the exact extent and characteristics of the neoplasm (Da Costa, 2009). There are few reports of surgical procedures in dogs with intramedullary neoplasms (Jeffery and Phillips, 1995;Ueno et al, 2006;Brewer et al, 2011;Liebel et al, 2011;Coelho et al, 2013). Knowing that, early diagnosis increases the chances of success in therapy and the combination of therapeutic modalities may offer a cure or prolonged survival (Da Costa, 2009;Bagley, 2010), as already reported in some cases, and ependymoma and nephroblastoma intramedullary treated with surgery associated with radiotherapy, which made it possible to increase the survival of these patients (Jeffery and Phillips, 1995;Ueno et al, 2006;Brewer et al, 2011;Liebel et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…33 A case series of 10 cases of canine nephroblastoma reported a post-treatment survival duration for the four cases of intramedullary nephroblastoma ranging from 38 to 269 days (median, 140 days). 34 These findings suggest that some canine intramedullary tumours are operable and that surgical management can prolong survival. As the spinal parenchyma has no nociceptors, 1 intramedullary masses generally do not cause pain.…”
mentioning
confidence: 98%